2019
DOI: 10.1099/mgen.0.000309
|View full text |Cite
|
Sign up to set email alerts
|

Pangenome of Acinetobacter baumannii uncovers two groups of genomes, one of them with genes involved in CRISPR/Cas defence systems associated with the absence of plasmids and exclusive genes for biofilm formation

Abstract: Acinetobacter baumannii is an opportunistic bacterium that causes hospital-acquired infections with a high mortality and morbidity, since there are strains resistant to virtually any kind of antibiotic. The chase to find novel strategies to fight against this microbe can be favoured by knowledge of the complete catalogue of genes of the species, and their relationship with the specific characteristics of different isolates. In this work, we performed a genomics analysis of almost 2500 strains. Two different g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 58 publications
3
59
0
Order By: Relevance
“…Amazingly, we found that the strains that amplify the CRISPR-Cas I-Fb system presented from 1 to 4 plasmids. According to Mangas et al (2019), there is an association between the presence of the CRISPR-Cas system and the absence of plasmids in A. baumannii genomes; as we could see in our results; these systems would limit the transfer of mobile elements such as plasmids.…”
Section: Discussionsupporting
confidence: 67%
“…Amazingly, we found that the strains that amplify the CRISPR-Cas I-Fb system presented from 1 to 4 plasmids. According to Mangas et al (2019), there is an association between the presence of the CRISPR-Cas system and the absence of plasmids in A. baumannii genomes; as we could see in our results; these systems would limit the transfer of mobile elements such as plasmids.…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies have emphasized the high genomic plasticity of A. baumannii and the role it plays in hospital adaptation and pathogenicity (9,11,12,47). This work, and more recent studies analyzing the diversity of thousands of genomes, estimate that the core genome of A. baumannii is comprised of ϳ2,200 genes, while its pangenome is projected to be in the region of 19,000 distinct genes (48). The fact that comparable numbers are observed with just the 100 isolates in this panel is a testament to the diversity of the MRSN repository.…”
Section: Discussionmentioning
confidence: 85%
“…Unlike the strains from group two, positive for a high number of plasmids, the strains from the first group contain mainly genes involved in regulating the elements of the CRISPR system. This finding led to the idea that the CRISPR system may be involved in the restriction of the plasmid entry into bacterial cells [ 334 ]. Karlapudi et al conducted an in silico study to understand the role of the AbaI gene in biofilm formation in A. baumannii .…”
Section: Innovative Strategies For Treatment Of a Baumamentioning
confidence: 99%